Anti-permeable acrylic waterproof emulsion paint and preparation method thereof

CN122278282BActive Publication Date: 2026-11-03JIAXING JIAHE WOOD IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610455423.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-08
Publication Date
2026-11-03
Estimated Expiration
2046-04-08

AI Technical Summary

Technical Problem

Conventional acrylic coatings have shortcomings in waterproofing performance, especially in their inability to effectively prevent water penetration, and they may crack over time, making it difficult to meet the waterproofing requirements of buildings.

Method used

Sisal fiber modified with natural biomass gum on its surface is used, and crosslinking monomers are prepared by a specific method to form a high-density, superhydrophobic coating structure. Combined with the hydrogen bond association network of fiber and acrylate molecular chains, the density and compressive strength of the coating are improved.

Benefits of technology

It improves the coating's waterproof performance and compressive strength, prevents moisture penetration and cracking, and enhances the coating's durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of paint, and discloses anti-permeation type acrylic waterproof emulsion paint and a preparation method thereof. The paint is prepared by mixing raw materials such as acrylic emulsion polymerization material and fiber modification material, wherein the acrylic emulsion polymerization material is added with crosslinking monomers in the preparation process, the crosslinking monomers can make the density of the prepared acrylic ester molecular chain higher, effectively prevent water from permeating, meanwhile, the fluorine element in the alternating structure of the crosslinking monomers and the tert-butyl benzene both have strong hydrophobicity, can form a super-hydrophobic layer on the surface of the coating, and can further enhance the waterproof performance of the coating, the fiber modification material can produce hydrogen bond association with the acrylic ester molecular chain, can more efficiently play the pulling effect of the fiber, can improve the compressive strength of the coating, can avoid the cracking of the coating under the action of external pressure, and can make it more difficult for water to permeate from the cracks caused by the cracking to the inside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating technology, specifically to an impermeable acrylic waterproof emulsion coating and its preparation method. Background Technology

[0002] Waterproofing is a crucial aspect of ensuring the structural safety and functionality of buildings. With rapid urbanization and continuous advancements in building technology, the demands on waterproofing materials are constantly increasing. Research has shown that acrylic polymers, with their excellent resistance to UV rays, acid rain, and air pollution, as well as superior high and low temperature performance, meet the waterproofing needs of different regions and seasons. Today, acrylic waterproofing emulsion coatings are widely used in waterproofing projects for various buildings, becoming an important choice for modern building waterproofing.

[0003] However, with the continuous development of materials science and technology, the shortcomings of conventional acrylic coatings in waterproofing have gradually become apparent. Moreover, with the increase in service life, acrylic coatings may crack and become unable to prevent water penetration, which has gradually limited their application in the field of building waterproofing. At present, the waterproofing modification of acrylic coatings is generally achieved by adding inorganic materials with a layered structure to extend the penetration path. However, the natural interface problem between inorganic materials and acrylic esters makes it difficult to achieve an efficient modification effect. Based on this, the present invention provides an acrylic waterproof emulsion coating that can solve the problems existing in the prior art. Summary of the Invention

[0004] In order to solve the problems mentioned in the background art, the purpose of this invention is to provide an impermeable acrylic waterproof emulsion coating and its preparation method.

[0005] The objective of this invention can be achieved through the following technical solutions: A waterproof acrylic emulsion coating with impermeability comprises the following raw materials measured in parts by weight: 72-85 parts acrylic emulsion polymer, 2.5-5.5 parts fiber modifier, 0.1-0.5 parts defoamer, and 0.2-1 parts leveling agent; The modified fiber material is sisal fiber with a surface modified with natural biomass gum.

[0006] As a further aspect of the present invention, the acrylic emulsion polymer is prepared by the following method: Step 1: Add the soft monomer, hard monomer, functional monomer, crosslinking monomer, emulsifier and deionized water to a reaction vessel filled with nitrogen, stir and mix evenly to form a premixed solution; Step 2: Control the temperature of the reactor at 50-60℃ and continuously stir and emulsify for 0.5-1h. Then add the initiator to the reactor. After the initiator is added, raise the temperature to 78-82℃ and continue stirring for 4-8h. Then cool down and discharge the material to obtain acrylic emulsion polymer.

[0007] As a further embodiment of the present invention, the soft monomer is ethyl acrylate or butyl acrylate; the hard monomer is ethyl methacrylate or methyl methacrylate; the functional monomer is acrylamide or acrylic acid; the emulsifier is sodium dodecylbenzenesulfonate or sodium dodecyl sulfate; and the initiator is azobisisobutyronitrile or azobisisoheptanenitrile.

[0008] As a further embodiment of the present invention, the mass ratio of the soft monomer, hard monomer, functional monomer, crosslinking monomer, emulsifier, deionized water and initiator is 10-25:4-8:1-2:0.5-1.5:1-1.5:60-80:0.1-0.2.

[0009] As a further aspect of the present invention, the crosslinking monomer is prepared by the following method: Step A: Add 3-(2,2,3,3-tetrafluoropropoxy)-1,2-propene oxide to a sulfuric acid solution with a pH of 2-3, stir until homogeneous, then stir at 80-90℃ for 1-1.5h, cool down and discharge, wash until neutral, and then vacuum dry to obtain the intermediate. Step B: Add the intermediate, 4-tert-butylphthalic anhydride, and N,N-dimethylformamide to the polymerization reactor, purge with nitrogen for protection, then raise the temperature to 40-50℃ and stir for 3-6 hours. Continue to add catalyst to the polymerization reactor and adjust the temperature to 90-100℃, stirring continuously for 12-18 hours. Adjust the temperature again to 30-40℃, then add acryloyl chloride to the polymerization reactor. After the addition is complete, keep warm for 2-4 hours, evaporate to remove the solvent, collect the product, and purify it to obtain the crosslinking monomer.

[0010] As a further aspect of the present invention, in step B, the molar ratio of the intermediate to 4-tert-butylphthalic anhydride is 1:0.9-0.95.

[0011] As a further aspect of the present invention, in step B, the catalyst is p-toluenesulfonic acid.

[0012] It should be noted that in the above technical solution, 3-(2,2,3,3-tetrafluoropropoxy)-1,2-propene oxide is first acidified with sulfuric acid solution to open the epoxy group and form two equivalent active hydroxyl groups as intermediates. These intermediates then undergo ring-opening with the maleic anhydride group in the 4-tert-butylphthalic anhydride structure to form an intermediate product containing both active hydroxyl and active carboxyl groups. Through the action of a catalyst, the active carboxyl and hydroxyl groups of the intermediate product undergo a self-condensation reaction. By controlling the amount of intermediates and 4-tert-butylphthalic anhydride, the self-condensation reaction can be made to exhibit hydroxyl-terminated end-capping. Finally, by using acryloyl chloride as a capping agent, a macromolecular substance with alternating links of two equivalent unsaturated alkenyl substituents at the structural ends can be obtained, i.e., a cross-linked monomer.

[0013] As a further aspect of the present invention, the fiber-modified material is prepared by the following method: Step S1: Add sisal fiber to toluene, and after ultrasonic dispersion, add chloroethyl isocyanate and dibutyltin dilaurate to the dispersion. After the addition is complete, heat to 60-70℃, keep warm and stir for 6-9 hours, filter out the solid material, and then wash and vacuum dry to obtain halogenated sisal fiber. Step S2: Disperse the halogenated sisal fiber in deionized water, then add tamarind gum. After the addition is complete, raise the temperature to 80-85℃, stir and mix evenly, then continue to add the accelerator. After the addition is complete, keep stirring for 4-8 hours, then stop heating, filter out the fiber material, and after washing and vacuum drying, obtain the modified fiber material.

[0014] As a further aspect of the present invention, the accelerator is triethylamine.

[0015] In the above technical solution, dibutyltin dilaurate is used as a catalyst to catalyze the amination reaction between chloroethyl isocyanate and the hydroxyl groups of sisal fiber, thereby modifying the halogen substituents on the surface of sisal fiber to obtain halogenated sisal fiber. Then, under the action of an accelerator, the halogen substituents of halogenated sisal fiber can be further replaced with the active hydroxyl groups of tamarind gum, thereby modifying the surface of biomass tamarind gum on the sisal fiber to obtain fiber modified material.

[0016] A method for preparing an impermeable acrylic waterproof emulsion coating includes the following steps: Step 1: Weigh each ingredient according to the specified weight proportions and set aside. The second step is to add the acrylic emulsion polymer, fiber modifier, and leveling agent to a high-speed mixer, adjust the speed to 300-500 rpm, and mechanically stir until completely mixed. Then, adjust the speed to 80-100 rpm, add the defoamer, stir for 10-20 minutes, let stand for 20-40 minutes, and then discharge the material.

[0017] The beneficial effects of this invention are: (1) The crosslinked monomer structure prepared by the present invention contains alternating tetrafluoropropoxy-tert-butylbenzene linkage structures. On the one hand, the acrylate molecular chain obtained by crosslinking the crosslinked monomer has a higher density and the coating formed by curing has a higher density, thus effectively preventing water penetration. On the other hand, the fluorine element and tert-butylbenzene in the alternating structure have extremely strong hydrophobicity, which can form a superhydrophobic layer on the coating surface, prevent water from lingering for a long time, and further enhance the waterproof performance of the coating.

[0018] (2) The present invention modifies the fiber by modifying the surface of sisal fiber with macromolecular biomass tamarind gum. Since the tamarind gum structure contains a large number of ether bonds, it can form hydrogen bonds with the acrylate molecular chain. Therefore, a micro hydrogen bond association network can be formed at the interface between the sisal fiber and the acrylate molecular chain, so that the sisal fiber can be firmly "embedded" in the coating network. This can more efficiently exert the fiber's traction effect, improve the compressive strength of the coating, and prevent the coating from cracking under external pressure, which would make it more difficult for water to penetrate into the interior through the cracks caused by the cracking.

[0019] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1 A waterproof acrylic emulsion coating with impermeability comprises the following raw materials measured in parts by weight: 72 parts acrylic emulsion polymer, 2.5 parts fiber modifier, 0.1 parts defoamer NYK-065, and 0.2 parts leveling agent BYK-310; The preparation method of the coating includes the following steps: Step 1: Weigh each ingredient according to the specified weight proportions and set aside. Step 2: Add the acrylic emulsion polymer, fiber modifier, and leveling agent BYK-310 to a high-speed mixer, adjust the speed to 300 rpm, and mechanically stir until completely mixed. Adjust the speed to 80 rpm, then add the defoamer NYK-065, stir for 10 minutes, let stand for 20 minutes, and then discharge.

[0022] The acrylic emulsion polymer is prepared using the following method: Step ①: Add 0.8g of 3-(2,2,3,3-tetrafluoropropoxy)-1,2-propene oxide to a sulfuric acid solution with pH 3, stir until homogeneous, then stir at 90℃ for 1 hour, cool down and discharge, wash until neutral, and then vacuum dry to obtain the intermediate. Step ②: Add 0.6g of intermediate, 0.55g of 4-tert-butylphthalic anhydride and N,N-dimethylformamide to the polymerization reactor, purge with nitrogen for protection, then raise the temperature to 45℃ and stir for 4h. Then add 0.1g of p-toluenesulfonic acid to the polymerization reactor and adjust the temperature to 100℃, continue stirring for 16h, then adjust the temperature to 35℃ again, and add 0.1g of acryloyl chloride to the polymerization reactor. After the addition is complete, keep warm for 3h, evaporate to remove the solvent, collect the product, and purify it to obtain the crosslinking monomer.

[0023] Step ③: Add 1.5g butyl acrylate, 0.6g methyl methacrylate, 0.15g acrylamide, 0.1g crosslinking monomer, 0.15g sodium dodecyl sulfate and 8g deionized water to a nitrogen-filled reactor and stir to mix evenly to form a premixed solution. Step 4: Control the temperature of the reactor at 55℃ and continuously stir and emulsify for 1 hour. Then add 0.01g of azobisisobutyronitrile to the reactor. After the addition is complete, raise the temperature to 80℃ and continue stirring for 6 hours. Then cool down and discharge the material to obtain acrylic emulsion polymer.

[0024] The fiber-modified material is prepared using the following method: Step S1: Add 2.6g of sisal fiber to toluene, and after ultrasonic dispersion, add 0.6g of chloroethyl isocyanate and 0.01g of dibutyltin dilaurate to the dispersion. After the addition is complete, heat to 65℃, keep warm and stir for 8 hours, filter out the solid material, and then wash and vacuum dry to obtain halogenated sisal fiber. Step S2: Disperse 1.5g of halogenated sisal fiber into deionized water, then add 2.5g of tamarind gum. After the addition is complete, raise the temperature to 80℃, stir and mix evenly, then add 0.2g of triethylamine. After the addition is complete, keep stirring for 6 hours, then stop heating, filter out the fiber material, and after washing and vacuum drying, obtain the modified fiber material.

[0025] Example 2 A waterproof acrylic emulsion coating with impermeability comprises the following raw materials measured in parts by weight: 78 parts acrylic emulsion polymer, 5 parts fiber modifier, 0.2 parts defoamer NYK-065, and 0.5 parts leveling agent BYK-310; The preparation method of the coating includes the following steps: Step 1: Weigh each ingredient according to the specified weight proportions and set aside. Step 2: Add the acrylic emulsion polymer, fiber modifier, and leveling agent BYK-310 to a high-speed mixer, adjust the speed to 400 rpm, and mechanically stir until completely mixed. Adjust the speed to 100 rpm, then add the defoamer NYK-065, stir for 20 minutes, let stand for 30 minutes, and then discharge.

[0026] The preparation methods for the acrylic emulsion polymer and the fiber-modified material are the same as in Example 1.

[0027] Example 3 A waterproof acrylic emulsion coating with impermeability comprises the following raw materials measured in parts by weight: 85 parts acrylic emulsion polymer, 5.5 parts fiber modifier, 0.5 parts defoamer NYK-065, and 1 part leveling agent BYK-310; The preparation method of the coating includes the following steps: Step 1: Weigh each ingredient according to the specified weight proportions and set aside. Step 2: Add the acrylic emulsion polymer, fiber modifier, and leveling agent BYK-310 to a high-speed mixer, adjust the speed to 500 rpm, and mechanically stir until completely mixed. Adjust the speed to 100 rpm, then add the defoamer NYK-065, stir for 20 minutes, let stand for 40 minutes, and then discharge.

[0028] The preparation methods for the acrylic emulsion polymer and the fiber-modified material are the same as in Example 1.

[0029] Comparative Example 1 An impermeable acrylic waterproof emulsion coating differs from Example 2 in that the fiber-modified material is replaced with unmodified sisal fiber, while the rest are the same.

[0030] Comparative Example 2 An impermeable acrylic waterproof emulsion coating differs from Example 2 in that the fiber-modified material is removed, while the rest are the same.

[0031] Comparative Example 3 An anti-seepage acrylic waterproof emulsion coating differs from Example 2 in that no crosslinking monomer is added during the preparation of the acrylic emulsion polymer; all other aspects are the same.

[0032] Test case The coatings from the examples and comparative examples were uniformly applied to the surface of tinplate and then placed in a temperature environment of 100°C until they were completely cured into a film. These films were then used as test samples for various performance tests. According to standard GB / T 1732-2020, the impact resistance of the samples was tested; According to standard GB / T 16777-2008, the waterproof performance was tested at a pressure of 0.3 MPa for 4 hours. The test results are recorded in Table 1: Table 1 According to the test results, the coating formed after curing of the coating prepared in this embodiment of the invention has good impact and crack resistance, and also exhibits excellent waterproof and seepage-proof effects. Replacing the fiber-modified material with unmodified sisal fiber results in certain interface problems, making it difficult for the sisal fiber to effectively exert its tensile and traction properties, thus negatively impacting the coating's impact and crack resistance. Complete removal of the fiber-modified material significantly reduces the material's impact resistance. Removing the crosslinking monomers from the acrylic emulsion polymerization process reduces the molecular chain density, leading to a decrease in the coating's compactness and consequently a significant reduction in its waterproof performance.

[0033] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.

[0034] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A waterproof acrylic emulsion coating with impermeability, characterized in that, Including the following raw materials measured in parts by weight: 72-85 parts acrylic emulsion polymer, 2.5-5.5 parts fiber modifier, 0.1-0.5 parts defoamer, and 0.2-1 parts leveling agent; The modified fiber material is sisal fiber with a surface modified with natural biomass gum; The acrylic emulsion polymer is prepared using the following method: Step 1: Add the soft monomer, hard monomer, functional monomer, crosslinking monomer, emulsifier and deionized water to a reaction vessel filled with nitrogen, stir and mix evenly to form a premixed solution; Step 2: Control the temperature of the reactor at 50-60℃ and continuously stir and emulsify for 0.5-1h. Then add the initiator to the reactor. After the initiator is added, raise the temperature to 78-82℃ and continue to stir and maintain the temperature for 4-8h. Then cool down and discharge the material to obtain acrylic emulsion polymer. The soft monomer is ethyl acrylate or butyl acrylate; the hard monomer is ethyl methacrylate or methyl methacrylate; the functional monomer is acrylamide or acrylic acid; the emulsifier is sodium dodecylbenzenesulfonate or sodium dodecyl sulfate; the initiator is azobisisobutyronitrile or azobisisoheptanenitrile. The mass ratio of the soft monomer, hard monomer, functional monomer, crosslinking monomer, emulsifier, deionized water and initiator is 10-25:4-8:1-2:0.5-1.5:1-1.5:60-80:0.1-0.2; The crosslinking monomer is prepared using the following method: Step A: Add 3-(2,2,3,3-tetrafluoropropoxy)-1,2-propene oxide to a sulfuric acid solution with a pH of 2-3, stir until homogeneous, then stir at 80-90℃ for 1-1.5h, cool down and discharge, wash until neutral, and then vacuum dry to obtain the intermediate. Step B: Add the intermediate, 4-tert-butylphthalic anhydride and N,N-dimethylformamide to the polymerization reactor, purge with nitrogen for protection, then raise the temperature to 40-50℃ and stir for 3-6 hours. Continue to add catalyst to the polymerization reactor and adjust the temperature to 90-100℃, continue stirring for 12-18 hours, then adjust the temperature to 30-40℃ again, and then add acryloyl chloride to the polymerization reactor. After the addition is complete, keep warm for 2-4 hours, evaporate to remove the solvent, collect the product, and purify it to obtain the crosslinking monomer. The molar ratio of the intermediate to 4-tert-butylphthalic anhydride is 1:0.9-0.95; The fiber-modified material is prepared using the following method: Step S1: Add sisal fiber to toluene, and after ultrasonic dispersion, add chloroethyl isocyanate and dibutyltin dilaurate to the dispersion. After the addition is complete, heat to 60-70℃, keep warm and stir for 6-9 hours, filter out the solid material, and then wash and vacuum dry to obtain halogenated sisal fiber. Step S2: Disperse the halogenated sisal fiber in deionized water, then add tamarind gum. After the addition is complete, raise the temperature to 80-85℃, stir and mix evenly, then continue to add the accelerator. After the addition is complete, keep stirring for 4-8 hours, then stop heating, filter out the fiber material, and after washing and vacuum drying, obtain the modified fiber material.

2. The impermeable acrylic waterproof emulsion coating according to claim 1, characterized in that, In step B, the catalyst is p-toluenesulfonic acid.

3. The impermeable acrylic waterproof emulsion coating according to claim 1, characterized in that, The accelerator is triethylamine.

4. A method for preparing the impermeable acrylic waterproof emulsion coating as described in claim 1, characterized in that, Includes the following steps: Step 1: Weigh out each ingredient according to the specified weight proportions and set aside. The second step is to add the acrylic emulsion polymer, fiber modifier, and leveling agent to a high-speed mixer, adjust the speed to 300-500 rpm, and mechanically stir until completely mixed. Then, adjust the speed to 80-100 rpm, add the defoamer, stir for 10-20 minutes, let stand for 20-40 minutes, and then discharge the material.

Citation Information

Patent Citations

  • Waterproof coating containing polyether-modified silicon-acrylic soft resin and preparation method thereof

    CN102146247A

  • Coloring composition, film, optical filter, solid-state imaging element, and image display device

    WO2023157740A1